Respostas
respondido por:
0
3x - 2y - 10 = 0
2x + y - 2 = 0
3x - 2y = 10
2x + y = 2
multiplica a segunda equação por 2
3x - 2y = 10
4x + 2y = 4
soma as duas..
7x = 14
x = 14 / 7
x = 2
como esse valor de x, achamos y
2x + y = 2
2.2 + y = 2
4 + y = 2
y = 2 - 4
y = - 2
S = {2, - 2}
O ponto de intercepção é 2, -2
2x + y - 2 = 0
3x - 2y = 10
2x + y = 2
multiplica a segunda equação por 2
3x - 2y = 10
4x + 2y = 4
soma as duas..
7x = 14
x = 14 / 7
x = 2
como esse valor de x, achamos y
2x + y = 2
2.2 + y = 2
4 + y = 2
y = 2 - 4
y = - 2
S = {2, - 2}
O ponto de intercepção é 2, -2
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás